Metodologi tafsir sains dan sosial ditinjau dari tafsir bil-ilmi - Zuhroidaturrahmah, Alfi (Maliki Interdisciplinary Journal, 2024)
The interpretation of the Qur’an that is developing in modern times like today uses more bil ilmi interpretation methods. This is due to the rapid progress of science and technology that existed in modern times at that time. It is said that this influence has a very significant impact. However, actually in the classical period or in earlier times, the development of the interpretation of the Qur’an, the method of interpreting the bil imi already existed. The presence of a method of interpreting the Qur’an using the bil ilmi interpretation method was not immediately expected. This discussion also reaps pros and cons. Of course, regardless of whether this method of interpreting bil ilmi is supported or rejected, information about the existence of science was explained late by Allah in several letters in the Koran. For example, this problem is related to the process of human creation.